Analisis Pengaruh Variasi Slice Thickness Terhadap Kualitas Citra pada Pemeriksaan CT Scan Kepala dengan Kasus Stroke Hemorragic di RS TK II Pelamonia Makassar Tahun 2023 - Dian Indrayani Solong; Ni Putu Rita Jeniyanthi; I Kadek Sukadana (Lembaga Pengembangan Kinerja Dosen, 2023)
Hemorrhagic stroke is the rupture of blood vessels in the brain, resulting in reduced blood flow (ischemia) and hypoxia. One of the disorders that can be diagnosed through sophisticated modalities is a CT scan, because it can be done quickly and accurately when evaluating bleeding in the brain. The slice thickness used in CT scans of the head in hemorrhagic stroke cases is 5 mm-10 mm, carried out using a one range protocol, namely from the basic cranii to the vertex. Slice thickness is the thickness of the slice that can be selected according to clinical needs. The factors used to evaluate image quality are spatial resolution, resolution contrast and noise. This research is quantitative by taking an experimental approach to analyze the effect of using slice thickness variations of 3mm, 4mm and 5mm on image quality (spatial resolution, resolution contrast and noise) on CT scans of the head in cases of hemorrhagic stroke of 10 samples. Based on the results of the research carried out, the researchers can conclude according to the overall results of the Friedman test that there is an influence on the image quality of CT scans of the head in hemorrhagic stroke cases using slice thickness variations of 3mm, 4mm and 5mm on spatial resolution, contrast resolution and noise. So based on the results of the Friedman test per image quality, there is a difference in the image quality of CT scans of the head and cases of hemorrhagic stroke which use slice thickness variations of 3mm, 4mm and 5mm. Based on the results of the mean rank of the Friedman test, slice thickness 5mm has a mean rank of 2.88 with the highest value. Based on the results of this study, researchers can recommend that CT scans of the head in cases of hemorrhagic stroke use a slice thickness of 5 mm with the aim that the image quality results in CT scans of the head in cases of hemorrhagic stroke look clear and good.